Trade Patterns in Food Imports to China: Commodities, Trends, and Shifts (1992-2020) - Castellanos-Curiel, Ricardo; Vallejo-Jiménez, Benjamín (México y la Cuenca del Pacífico, 2023)
Our research unveils how China’s food-related imports from 1992 to 2020 changed in composition by decreasing the imports of some commodities in favor of others. Their origins suggest that some countries are being substituted as commercial partners for specific commodities. We empirically identified outliers by setting interquartile limits at the commodity level and by origin. Unit-root and normality tests were applied. Finally, Spearman or Pearson correlation coefficients were computed where appropriate. Results indicate that imports are stabilizing during the studied period. China increased its imports of Sugar and cereals to the detriment of edible preparations, live animals, trees, and oilseeds. Some Asian countries are capturing part of the market once dominated by North America or Europe. Finally, lower dependence on partners was found for meat, gums, cocoa, and edible preparations. This methodology might help those analyzing the effects of trade agreements, country specialization, and strategic decisions.